2006
DOI: 10.5194/angeo-24-3533-2006
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of the location and width of Saturn's southern auroras

Abstract: Abstract.A selection of twenty-two Hubble Space Telescope images of Saturn's ultraviolet auroras obtained during [1997][1998][1999][2000][2001][2002][2003][2004] has been analysed to determine the median location and width of the auroral oval, and their variability. Limitations of coverage restrict the analysis to the southern hemisphere, and to local times from the post-midnight sector to just past dusk, via dawn and noon. It is found that the overall median location of the poleward and equatorward boundaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
105
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 40 publications
18
105
0
Order By: Relevance
“…From an analysis of the latter current system, Cowley and Bunce (2003) concluded that the corotation-enforcement currents at Saturn are too weak and occur at too low a latitude to explain the observed UV auroras, and thus suggested that a solar windrelated origin was the more likely. These results have subsequently been amplified by further modelling work presented by Cowley et al (2004b), and also by the statistical analysis of the location of the UV auroras presented by Badman et al (2006), who showed that they occur well poleward of the latitude where the magnetospheric plasma departs from near-rigid corotation according to Voyager data.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…From an analysis of the latter current system, Cowley and Bunce (2003) concluded that the corotation-enforcement currents at Saturn are too weak and occur at too low a latitude to explain the observed UV auroras, and thus suggested that a solar windrelated origin was the more likely. These results have subsequently been amplified by further modelling work presented by Cowley et al (2004b), and also by the statistical analysis of the location of the UV auroras presented by Badman et al (2006), who showed that they occur well poleward of the latitude where the magnetospheric plasma departs from near-rigid corotation according to Voyager data.…”
Section: Introductionmentioning
confidence: 87%
“…We can also compare these calculated open field boundaries with the typical position of the UV oval determined by Badman et al (2006). These authors presented an analysis of a selection of twenty-two HST images of Saturn's auroras obtained during [1997][1998][1999][2000][2001][2002][2003][2004], including the images shown here in Fig.…”
Section: Comparison With Auroral Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping the distances of 8, 10, and 12 R S from the equatorial crossing point to the Saturn's southern ionosphere using the Khurana model and assuming an ionosphere 1000 km above Saturn's ellipsoid. Also shown are locations of the southern auroral boundaries as found from HST observations [Badman et al, 2006] and the 20 R S orbit of Titan. The grid shows planetocentric colatitude as the radial coordinate and local time as the azimuthal coordinate (sun toward right).…”
Section: Discussionmentioning
confidence: 99%
“…The Khurana field model was traced from the equator to the ionosphere using the same techniques used to map the pitch angle distributions. Figure 7 exhibits mapping [Badman et al, 2006].…”
Section: Discussionmentioning
confidence: 99%